The Effectiveness of Coordination on Disaster Management By the Goverment Disaster Agency in Ogan Ilir Regency - Nomaini, Faisal; Thamrin, Muhammad Husni; Budiarto, Gatot (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
Effective Natural Disaster Management Activities are prioritized targets at the National and regional levels. Implementing natural disaster management activities in certain regions are the regional government through the Regional Disaster Management Agency (BPBD). Apart from being the spearhead for implementing natural disaster management activities, BPBD also acts as a coordinator for other related agencies in the natural disaster management. The Regional Government of Ogan Ilir Regency as the study locus of the research which is the main data source for this article, has the problem of weak coordination function between BPBD and other agencies in natural disaster management activities. To ensure this problem, this research has been conducted on the effectiveness of the coordination function using a quantitative design through a survey of the BPBD and agencies involved in natural disaster management activities. The effectiveness of the coordination function as a variable is viewed in four dimensions, namely the unity of action, communication, division of labor, and discipline. From the results of two-dimensional research, the coordination function obtained effectiveness in the medium category and the other two dimensions gained effectiveness in the low category. Meanwhile, overall the achievement of the level of effectiveness of the coordination function in natural disaster management activities in the Ogan Ilir Regency Government is moderate (the effectiveness of the coordination function is moderate). Keywords: BPBD, Natural Disasters, Coordination Function.